2007
DOI: 10.1016/j.ijsolstr.2007.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Surface electro-elastic Love waves in a layered structure with a piezoelectric substrate and a dielectric layer

Abstract: The existence and behaviour of electro-elastic surface Love waves in a structure consisting of a piezoelectric substrate of crystal classe 6, 4, 6 mm, 4 mm, 622 or 422, an elastic layer and a dielectric medium is considered. The mathematical model obtained includes all the above crystal classes, i.e. the surface wave problems related to all these classes are presented in a single mathematical model. The dispersion equation for the existence of Love surface waves with respect to phase velocity is obtained. A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 12 publications
0
39
0
2
Order By: Relevance
“…A method of a spherical acoustic transducer that consists of a piezoelectric sphere substrate and an elastic coating is presented by Georgea and Ebenezer. 31 Danoyan and Piliposian 32 have discussed the existence and behavior of electro-elastic Love waves in a piezoelectric substrate with dielectric coating. Feng and Li 33 pointed out that surface electro-elastic SH waves can also propagate in the dielectric-piezoelectric structures.…”
Section: Introductionmentioning
confidence: 99%
“…A method of a spherical acoustic transducer that consists of a piezoelectric sphere substrate and an elastic coating is presented by Georgea and Ebenezer. 31 Danoyan and Piliposian 32 have discussed the existence and behavior of electro-elastic Love waves in a piezoelectric substrate with dielectric coating. Feng and Li 33 pointed out that surface electro-elastic SH waves can also propagate in the dielectric-piezoelectric structures.…”
Section: Introductionmentioning
confidence: 99%
“…According to the material properties and stacking sequence of the layer and the substrate, the layer/substrate layered structures considered in the literature can be classified into three forms, i.e. elastic layer/piezoelectric substrate, [6][7][8][9][10][11][12][13][14][15][16] piezoelectric layer/elastic substrate [17][18][19][20][21][22][23][24] and piezoelectric layer/piezoelectric substrate. [25][26][27][28][29][30] In the aforementioned works, most of the piezoelectric materials belong to the crystals of class 6 mm (including the piezoelectric ceramics).…”
Section: Introductionmentioning
confidence: 99%
“…6-9,17- showed that the cut angle of the substrate have a substantial influence on the dispersion properties. Danoyan and Piliposian 13 carried out the rigorous analysis for the existence of Love waves in a piezoelectric substrate of crystal class 6, 4, 6mm, 4mm, 622 or 422 with a soft dielectric layer. Subsequently, they 14 further examined the existence of Love wave in a layered medium composed of a hard dielectric layer on a piezoelectric half-space with 6, 4, 6mm or 4mm symmetries.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high performance, many such devices adopt layered piezoelectric structures consisting of a piezoelectric layer and an elastic substrate or an elastic layer and a piezoelectric substrate. Much research work has been done on the propagation of the transverse surface waves in such layered structures [2][3][4][5][6][7][8][9]. Due to the intrinsic brittle property of ceramic materials and the thermal mismatch between layer and substrate, however, initial stresses appear inevitably in such layered structures during the manufacture process and have significant effects on the propagation behavior of the transverse surface waves [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%